Tata Kelola Perusahaan dan Pengungkapan Tanggung Jawab Sosial Perusahaan pada Bank Komersial di Indonesia - Natalis Christian; Afifah Restalia Putri (Universitas Jember, 2023)
This study aims to explore the level and nature of corporate social responsibility (CSR) disclosure reporting practices in Indonesian commercial banks, as well as investigate the effect of board characteristics on CSR disclosure in the era of developing economies. Data collection in this study was collected manually from the annual reports of all commercial banks listed on the official website of the Indonesia Stock Exchange (IDX) in the period 2017 to 2020, so this research is included in a quantitative approach. Empirical evidence shows that board size and independent directors have a positive effect on CSR disclosure, while board gender diversity has no impact on CSR disclosure levels. Furthermore, the results of the study state that the age of the bank is a significant factor in the spread of CSR disclosure. In addition, the findings show that banks with managerial ownership, foreign share ownership and also state share ownership state extensive and transparent information about CSR activities. Keywords: Banking, Board Characteristics, Corporate Social Responsibility, Ownership Structure